Cadaveric study: study of lateral circumflex femoral arterial origin in Rajkot - Chauhan, Pradip Rameshbhai; Dangar, Khima P.; Rathwa, Ashish J.; Adhvaryu, Monika A.; Chauhan, Alpa P.; Rathod, Suresh P. (International Journal of Research in Medical Sciences, 2017)
Background: Lateral circumflex femoral artery contributes cruciate, trochanteric and knee joint anastomosis. In addition Lateral circumflex femoral artery flaps are used for the reconstruction of large tissue loss in the head and neck region, aortopopliteal bypass, coronary artery bypass grafting and extracranial intracranial bypass surgery. This work was carried out (a) to study the origin of lateral circumflex femoral artery and (b) to measure and compare (between male and female) the circumference at its origin. Methods: In this cross sectional study, 51 femoral triangles from 26 (18 male and 08 female) human adult cadavers were dissected and studied at P.D.U. government medical college, Rajkot, Gujarat. Site of origin of lateral circumflex femoral artery was identified and noted. The distance of origin of the artery from the origin of profunda femoris artery was measured and noted. Circumference at the level of origin was measured and diameter was calculated. Collected data was analysed by standard statistical formulas with the help of Microsoft excel 2013 and Epi info 7TM software. Results: 90.19% lateral circumflex femoral arteries originated from the profunda femoris artery and remaining 9.81% from the femoral artery. The mean distance of origin of the artery from the origin of profunda femoris artery was 18.44 mm. Lateral circumflex femoral artery circumference and diameter were significantly different between male and female (95% confidence interval, P <0.05). Conclusion: In this presented study maximum distance of origin of the artery from the origin was 65 mm while minimum distance of origin was 6 mm. In addition difference in circumference of the artery was statistically significant.